The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.energyfuels.5b00607
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Phase Stability of Biomass Fast Pyrolysis Bio-oils

Abstract: Fast pyrolysis bio-oil oil is a promising alternative to fossil fuels and is currently entering the heating oil market. However, there is a lack of available information about the phase stability of bio-oil. The water-soluble and water-insoluble compounds in bio-oil can either be in one homogeneous phase or form two individual phases, to which we refer to as phase separation. Phase separation can occur immediately after condensation of the pyrolysis vapors to bio-oil because of certain pyrolysis conditions or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 21 publications
2
101
0
Order By: Relevance
“…Despite some high value-added chemicals are found in the biooil, which includes hydrocarbons, alcohols, furans, phenols and so forth, its application is still limited as a consequence of the high oxygen content, low caloric value, high corrosion behavior and chemical instability [3,4]. Upgrading of biomass derived bio-oil provides an effective and efficient process to attain an energy benefit with a minimum effect on environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite some high value-added chemicals are found in the biooil, which includes hydrocarbons, alcohols, furans, phenols and so forth, its application is still limited as a consequence of the high oxygen content, low caloric value, high corrosion behavior and chemical instability [3,4]. Upgrading of biomass derived bio-oil provides an effective and efficient process to attain an energy benefit with a minimum effect on environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…The BcPO is acidic and its storage stability is limited because of the presence of acids and polymerisation reactions of reactive aldehydes with phenolics. Thus, the direct use as transportation fuel, or co‐feeding in conventional oil refineries, has still several barriers to be tackled.…”
Section: Figurementioning
confidence: 99%
“…It contains as ubstantial amounto fw ater and oxygen-containing compounds,w hich impliesal ow heating value as well (estimated at 40-50 %o f that for hydrocarbon fuels). [1] TheB cPO is acidic and its storage stability is limited [1,[5][6][7] because of the presence of acids and polymerisation reactions of reactive aldehydes with phenolics.T hus,t he direct use as transportation fuel, or co-feeding in conventional oil refineries,h as still severalb arriers to be tackled. Therefore, to extend the application prospects,u pgrading of BcPO is crucial.…”
mentioning
confidence: 99%
“…A correlation between the reaction water and the content of minerals in the biomass can be established. In their investigation, Oasmaa et al concluded that the bio‐oil produced from feedstocks with an ash content below 1.0 wt% typically consists of one phase and above 2 wt% likely separate into two phases . As agricultural residues have higher contents of catalytically active alkali metals compared to forest residues and soft woods, the bio‐oils obtained from them will also have higher water content, and thus a phase separation is to be expected.…”
Section: Introductionmentioning
confidence: 99%
“…In their investigation, Oasmaa et al concluded that the bio-oil produced from feedstocks with an ash content below 1.0 wt% typically consists of one phase and above 2 wt% likely separate into two phases. 12 As agricultural residues have higher contents of catalytically active alkali metals compared to forest residues and soft woods, 13 the bio-oils obtained from them will also have higher water content, and thus a phase separation is to be expected. This paper investigates the bio-oil production from two different feedstocks: a mixture of barley and wheat straw and miscanthus using an ablative hot surface reactor system.…”
Section: Introductionmentioning
confidence: 99%